High-Order Visual Processing, Visual Symptoms, and Visual Hallucinations: A Possible Symptomatic Progression of Parkinson's Disease - Barrell, Kelsey; Bureau, Britta; Turcano, Pierpaolo; Phillips, Gregory D.; Anderson, Jeffrey S.; Malik, Atul; Shprecher, David; Zorn, Meghan; Zamrini, Edward; Savica, Rodolfo (Frontiers in Neurology, 2018)
Objective: To determine whether Parkinson disease (PD) patients with visual hallucinations have different clinical characteristics and gray-matter volume than those with visual misperceptions or other visual symptoms. Background: The spectrum of visual complaints in PD is broad and complex. Methods: We conducted a retrospective chart review of 525 Parkinson disease patients to identify the frequency of visual symptoms and the association with clinical and radiological features. Brain volumetric MRI data was analyzed using multivariate logistic regression to differentiate cases with and without visual symptoms. Results: Among 525 PD cases, visual complaints were documented in 177 (33.7%). Among these, 83 (46.9%) had visual hallucinations, 31 (17.5%) had visual misperceptions, and 63 (35.6%) had other visual symptoms (diplopia, blurry vision, photophobia, dry eyes and eye pain or soreness). When compared to other visual symptoms, patients with visual hallucinations had significantly higher age, duration of disease, rate of REM sleep behavior disorder, and cognitive impairment. Visual hallucinations patients had decreased age-adjusted volumetric averages in 28/30 gray-matter regions when compared to Parkinson disease without visual symptoms and 30/30 gray-matter regions when compared to visual misperceptions patients. Conclusions: Visual symptoms in PD may represent a spectrum from other visual symptoms to visual misperceptions to visual hallucinations, with progression of the latter associated with older age, duration of disease, presence of REM sleep behavior disorder, cognitive impairment, and decreased gray-matter volume.